Socialization of Making Job Application Letters, Curriculum Vitae and Interview Preparation and Understanding Psychological Testing for High School Students: Human Resource - Marlita, Devi; Handayani, Sinai; Perwitasari, Erni Pratiwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
In order to carry out the tri dharma of higher education and As an effort to improve the quality of prospective senior high school graduates, the Trisakti Transportation and Logistics Institute research lecturer team was called upon to carry out this. Community Service by holding events whose topics are tailored to the needs of students as basic knowledge and preparation before entering the world of work. For this reason, educational institutions also pay special attention to prospective high school graduates who are expected to be ready and more confident when they enter the work industry. The method presented in the program above is through offline outreach and education, and the implementation of the activities will be carried out at State High Schools.